2021
DOI: 10.1177/26330040211022033
|View full text |Cite
|
Sign up to set email alerts
|

They’ve been BITTEN: reports of institutional and provider betrayal and links with Ehlers-Danlos Syndrome patients’ current symptoms, unmet needs and healthcare expectations

Abstract: Introduction: Patients with rare and/or care-intensive conditions, such as Ehlers-Danlos Syndrome (EDS), can pose challenges to their healthcare providers (HCPs). The current study used the BITTEN framework1 to code EDS patients’ open-ended written responses to a needs survey to determine their self-reported prevalence of healthcare institutional betrayal and its link with their expressed symptoms, provider perceptions, unmet needs, and on-going healthcare-related expectations. Methods: Patients with EDS ( n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The second most common theme was negative attitudes from healthcare professionals, including being dismissed, ignored, belittled, and blamed. Others have described this as "healthcare-related institutional betrayal" because it involves a violation of the patient's trust that healthcare providers will act in the patient's best interest [17]. Accessibility/convenience and financial aspects, two themes derived from the PSQ-18, followed negative attitudes as the most reported themes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second most common theme was negative attitudes from healthcare professionals, including being dismissed, ignored, belittled, and blamed. Others have described this as "healthcare-related institutional betrayal" because it involves a violation of the patient's trust that healthcare providers will act in the patient's best interest [17]. Accessibility/convenience and financial aspects, two themes derived from the PSQ-18, followed negative attitudes as the most reported themes.…”
Section: Discussionmentioning
confidence: 99%
“…In one small mixed-methods study of 28 patients with hEDS and HSD, participants reported poor quality physical therapy for joint hypermobility issues [16]. In another mixed-methods study (N = 234), almost half of the participants (45%) reported having unmet medical needs, and nearly half of those reported experiencing institutional betrayal, including professionals' lack of knowledge or willingness to learn about EDS [17]. Finally, in a recent study examining satisfaction with chronic illness care among HSD and EDS patients from both the US and Canada, participants had scores below the midpoint on almost all scales assessing chronic illness care (e.g., goal setting, follow-up/ coordination) [18].…”
Section: Healthcare Experiences Among Adults With Hypermobile Ehlers-...mentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from this study suggest that there are several specialties that diagnose EDS/HSD, and similar to previous reports, health care utilization among adults and minors with EDS/HSD is high due to the many comorbidities that occur. Many respondents obtain care from several subspecialties across many medical institutions which may lead to fractured, poorly coordinated care that does not meet the patient's needs, and leads to lack of trust in healthcare providers and negative expectations for healthcare needs (Langhinrichsen-Rohling et al, 2021). This represents a unique opportunity to develop specialized multidisciplinary care for adults and minors with EDS/HSD, that can address their specific needs and provide a foundation to better understand the patients' needs and develop better, coordinated care to meet the needs of those with EDS/ HSD.…”
Section: Discussionmentioning
confidence: 99%
“…In line with management of pediatric chronic conditions, the HCU pattern observed in the current study supports a shift from diagnostic to rehabilitative care over time; HCU became more treatment focused from prediagnosis to postdiagnosis, following current clinical recommendations for this population. Patients with EDS-HT often report experiencing a lack of awareness from healthcare professionals and difficulty accessing appropriate treatment in the healthcare system (Langhinrichsen-Rohling et al, 2021;Terry et al, 2015). Thus, creating efficient processes for referral, diagnostic evaluation, education for families, and prioritization of treatment services remains an ambitious but necessary goal.…”
Section: Discussionmentioning
confidence: 99%